2010
DOI: 10.1021/ie100288h
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Chemical Processes: A Graphical Approach to Process Synthesis To Improve Reactive Process Work Efficiency

Abstract: To reduce carbon dioxide emissions for chemical processes, one should make them as reversible as possible. Patel et al. [Ind. Eng. Chem. Res. 2005, 44, 3529−3537] showed that, in some cases, one can analyze processes in terms of their work and heat requirements. In particular, for processes, there exists a temperature that is called “the Carnot temperature”, at which one can satisfy the work requirement for the process, using the heat that must be added or removed. The analogy of a heat engine and Carnot tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…In other works (Sempuga et al, 2010;Fox et al, 2013) it has been shown how once one has this target material balance one can synthesise a process flow-sheet using what has been termed the "gh-diagram". As this is just a two dimensional plot no matter how complex the process this is a relatively simple procedure.…”
Section: Resultsmentioning
confidence: 98%
“…In other works (Sempuga et al, 2010;Fox et al, 2013) it has been shown how once one has this target material balance one can synthesise a process flow-sheet using what has been termed the "gh-diagram". As this is just a two dimensional plot no matter how complex the process this is a relatively simple procedure.…”
Section: Resultsmentioning
confidence: 98%
“…Similar evaluations concluded that the cost was 18-37 Euro for a pre-combustion technology using IGCC, and 13-30 Euro for an oxy-fuel process (Petrakopoulou et al, 2010;Adanez et al, 2012). Chemical looping combustion significantly improves the energy conversion efficiency, in terms of electricity generation (Ekstrom et al, 2008), because it improves the reversibility of the fuel combustion process through two linked parallel processes (Anheden and Svedberg, 1998;McGlashan, 2008;Sempuga et al, 2010Sempuga et al, , 2011.…”
Section: Introductionmentioning
confidence: 83%
“…From the enthalpy and Gibbs free energy values for the methane steam reforming it is possible to calculate the “Carnot Temperature” for this material balance. The Carnot Temperature is the temperature at which an independent material balance, process or reaction could be operated reversibly as a heat engine. The Carnot Temperature for Methane Steam Reforming is Tcarnot,MSR=960 normalK …”
Section: Development Of a Fischer‐tropsch Process Flowsheetmentioning
confidence: 99%